Genetic and environmental risk factors for Parkinson's disease in a Chinese population. Issue 5 (1st November 1998) - Chan, D K Y; Woo, J; Ho, S C; Pang, C P; Law, L K; Ng, P W; Hung, W T; Kwok, T; Hui, E; Orr, K; Leung, M F; Kay, R
Abstract : An epidemiological study of the environmental and genetic factors as well as the possible interplay between them was conducted among 215 patients with Parkinson's disease and 313 controls in a Chinese population in Hong Kong. In univariate analysis, a regular tea drinking habit was found to be a protective factor, which had not been reported before. Smoking (a protective factor), family history, duration of pesticide exposure (in years) in farming and pesticide exposure during farming in women (both risk factors) have been reported previously. In multivariate analysis, current smoking reached borderline significance at the 5% level and the variables, years exposed to pesticides and family history were significant at the 10% level. By contrast with the common occurrence of polymorphism of the CYP2D6 gene (a gene involved with xenobiotic metabolism) in white people, it is very rare in China and is not thought to be a significant factor contributing to Parkinson's disease in Chinese people.